APPLICATION OF THE LOYAL COOPERATION PRINCIPLE IN PUBLIC ADMINISTRATION - Vasilica NEGRUȚ; Ionela Alina ZORZOANĂ (Challenges of the Knowledge Society)
The aim of this study is to highlight the significance of the loyal cooperation principle in public administration (and not only). In order to achieve the objectives of this approach, using the comparative and logical method, we shall analyse specific legislation, specialized literature, CCR decisions, but also the relevant CJEU case-law. The analysis shall have as a starting point the principle of separation of powers in the rule of law, a principle with a rich history in the doctrine, and then we shall come to the emergence and development of the increasingly strong concept of „loyal cooperation″. Thus, we reach the point where such has been elevated to the rank of principle, first at European level by art. 4 para. (3) TEU, and subsequently the CJEU has developed a constant practice with reference to the application of this principle, often alongside two other principles, that of equivalence and that of effectiveness. In a generally accepted definition, the principle of loyal cooperation has been defined as the Union and the Member States, acting within the limits of their competences, must assist each other in the performance of this task. At national level, starting from the provisions of art. 1 para. (4) of the Romanian Constitution, according to which the State is organised according to the principle of the separation and balance of the legislative, executive and judicial powers within constitutional democracy, in the CCR case-law, the principle of loyal cooperation has increasingly been outlined, which has been considered as „an extension of the principle of the separation and balance of the legislative, executive and judicial powers within constitutional democracy″ (dec. no. 1431/03.11.2010, published in the Official Gazette of Romania, Part I, no. 758/12.11.2010). Furthermore, with the appearance of the Administrative Code, in Part III, dedicated to local public administration, among the principles applicable to local public administration, art. 75 para. (1) lit. e), the principle of collaboration. Starting from this, a first question naturally arises: why did the legislator feel the need to expressly mention this principle in the situation of local public administration? Should collaboration not be valid in public administration in general? On the other side, the (obviously loyal) cooperation principle would not even need to be expressly regulated, as it is, in my opinion, the very essence of good administration. In a second view, we shall try to examine whether and to what extent the loyal cooperation principle enshrined in the CCR decisions is also fully valid at the level of public administration, or whether it exclusively refers to the relationship between the three branches of the rule of law (legislative, judicial and executive) and the relationship between them.